The Status of Civil Servants' Pension Fund Inheritance: A Comparative Fiqh Study between Bahtsul Masa'il NU and the Majelis Tarjih Muhammadiyah - Abdul Rohim (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
One way to acquire wealth in Islam is through inheritance, where the estate left by a deceased person is distributed to their heirs based on Islamic principles of justice. However, in practice, disputes often arise regarding the status of a civil servant's (PNS) pension upon their death-whether it should be considered inheritance (tirkah) or not. This study aims to examine the principles of inheritance in Islamic law and analyse the views of Bahtsul Masail NU and Majelis Tarjih Muhammadiyah regarding the status of civil servant pensions. This research is library-based and employs a descriptive-analytical comparative method. The findings reveal that both organisations agree that a civil servant pension is not part of the tirkah and cannot be inherited in the traditional sense, but rather belongs to designated recipients such as the spouse or children. The difference lies in their methodological approaches: NU refers to the fatwas of scholars (qaul), while Muhammadiyah relies on the general (mujmal) wording of hadith. Both organisations also agree that Indonesia's regulations on civil servant pensions are not in conflict with Islamic law